‘I feel the irritation and frustration all over the body’ Affective ambiguities in networked parenting culture - Lehto Mari; Paasonen Susanna (Sage Journals, 2025)
This article investigates the affective power of social media by analysing everyday encounters with parenting content among mothers. Drawing on data composed of diaries of social media use and follow-up interviews with six women, we ask how our study participants make sense of their experiences of parenting content and the affective intensities connected to it. Despite the negativity involved in reading and participating in parenting discussions, the participants find themselves wanting to maintain the very connections that irritate them, or even evoke a sense of failure, as these also yield pleasure, joy and recognition. We suggest that the ambiguities addressed in our research data speak of something broader than the specific experiences of the women in question. We argue that they point to the necessity of focusing on, and working through affective ambiguity in social media research in order to gain fuller understanding the complex appeal of platforms and exchanges.